Internet addiction and depression among students at residential college: readiness to seek counselling services - Ahmad, Nur Fatihah; Kamarudin, Engku Mardiah Engku; Mahmud, Mohd Izwan; Afdal; Noor, Amelia Mohd; Alam, Atiqah Puteri Mohd (UiTM Press, 2024)
Abstract: In contemporary society, the ubiquitous use of the Internet has become an unavoidable aspect of daily life. However, unregulated usage carries the potential for addiction, leading to a heightened sense of disconnection from the tangible world of technology. This empirical investigation conducted a quantitative exploration to establish the connection between Internet addiction, depression, and the willingness to utilise counselling services among the student body affiliated with one of Universiti Putra Malaysia’s residential colleges. The sample, consisting of 283 students, was meticulously selected through random sampling and represented a spectrum from first-year to final-year students. Data collection was executed through a structured questionnaire comprising three distinct instruments: the Internet Addiction Test (IAT), the Beck Depression Inventory (BDI), and the Attitudes Towards Seeking Professional Psychological Help-Short Form (ATSPPH-SF) inventory. A preliminary analysis of the data, conducted descriptively, revealed prevailing trends. The majority of respondents demonstrated a moderate inclination toward seeking counselling assistance. Simultaneously, they exhibited varying degrees of Internet addiction, ranging from moderate to high levels, and experienced depression at minimal to low levels. Subsequent correlation analysis has contributed noteworthy findings. It discerned pronounced negative correlations between the severity of Internet addiction, the presence of depression, and the readiness to pursue psychological counselling among the surveyed students. In light of these revelations, it is imperative for all stakeholders within the university ecosystem, including counsellors and the management of residential colleges, to foster synergistic collaboration. This collective effort assumes paramount importance in its mission to enhance the mental well-being and psychological health of the university’s student population.